The Neonatal Assessment Manual scorE: A Reliability Study on Hospitalized Neonates - Manzotti, Andrea; Cerritelli, Francesco; Lombardi, Erica; La Rocca, Simona; Biasi, Pamela; Chiera, Marco; Galli, Matteo; Lista, Gianluca (Frontiers in Pediatrics, 2021)
Despite clinical improvements in neonatal intensive care units (NICUs), prematurity keeps causing several comorbidities. To enhance the management of such conditions, in previous studies we devised the Neonatal Assessment Manual scorE (NAME) model, a structured touch-based assessment that aims to evaluate how newborns respond to gentle touch-based stimuli. The present study aimed to begin assessing the NAME interrater reliability and specific agreements. At the “Vittore Buzzi” Paediatric Hospital NICU ward in Milan, Italy, we enrolled 144 newborns, 85 male and 59 female, with a mean age of 35.9 weeks (±4.1) and a weight of 2055.3 gr (±750.6). Two experienced manual professionals performed the NAME procedure on all the infants. Regarding the total sample and the analysis by sex, we found moderate and statistically significant results for the interrater reliability (p<0.001) and the specific agreements (p<0.05), in particular for the “Marginal” score. Furthermore, interrater reliability significantly (p<0.05) increased as age and weight increased, whereas there was an almost constant moderate and significant (p<0.05) agreement especially for the “Marginal” score. Therefore, we found preliminary results that the NAME could be a reliable diagnostic tool for assessing the newborns’ general condition.